“It Must Happen in France” - Alexandre Monnin (ARQ, 2022)
Monnin has argued elsewhere to restore, close, and relocate the heritage of our planet’s collapsing livelihood and dismantle the old: the north. This text discusses the location of ideas of civilization, past and present, and claims that the north must consider itself as the witness of obsolete futures. It aims for an entire ecological redirection, recognizing the negative commons of existing infrastructural and technological models. Doing so, summons the north, and France, to learn and dismantle these models through themselves.